Sustainability performance measurement with Analytic Network Process and balanced scorecard: Cuban practical case - Medel-gonzález, Frank; García-Ávila, Lourdes Francisca; Salomon, Valério Antonio Pamplona; Marx-gómez, Jorge; Hernández, Cecilia Toledo (Associação Brasileira de Engenharia de Produção, 2016)
Abstract The recent years has arisen a global discussion in relation with how to incorporate sustainability at a business level. Corporate sustainability is a multidimensional concept, is the translation of Sustainable Development concept at a business level. Sustainability in organizations must be managed and assessed by decision makers, for that reason a multi-criteria sustainability performance measurement is necessary. The aim of this paper is combine different important tools that helps to make operative corporate sustainability and sustainability performance measurement in Cuban organizations. The combination of Sustainability Balanced Scorecard, multi-criteria decisions models like: Analytic Network Process, and Matrix of Sustainable Strategic Alignment, can help managers in sustainability performance measurement and assessment. The result of this paper focus in a Corporate Sustainability Measurement Network design as a first approach for further sustainability performance measurement systems development emphasizing in multi-criteria analysis.
Keywords: Sustainability performance; Measurement network; Analytic Network Process